Social Media in Electoral Communication: A Case Study of Strategic Initiatives by Bantul Election Commission for the 2024 Elections - Sari, Eka Anisa; Setiawan, Resdika Anggesa Dwi; Jandevi, Uspal (CHANNEL: Jurnal Komunikasi, 2023)
In the contemporary landscape of democratic processes, the role of social media has become instrumental in shaping political communication strategies. This study investigates the nuanced dynamics of social media utilization, with a specific focus on its impact on the effectiveness of communication strategies employed during the 2024 Elections by the Bantul Election Commission (KPU Bantul) in Indonesia. Recognizing the potential of social media in enhancing voter participation, KPU Bantul strategically employed platforms such as Instagram, websites, and YouTube to educate, engage, and mobilize the public. Through a qualitative analysis rooted in social media theory and communication strategy frameworks, this research explores the innovative methods used by KPU Bantul. Key findings encompass strategic networking and coordination, digital literacy initiatives targeting novice voters, challenges in measuring social media impact, and the transformative potential of integrating social media within electoral processes. The study not only sheds light on the intricate mechanisms of social media utilization but also offers practical insights for improving social media initiatives in future electoral contexts.